Approche couplée éléments discrets/finis pour la simulation d’un impact sur ouvrage - Frangin, Emmanuel; Marin, Philippe; Daudeville, Laurent (European Journal of Computational Mechanics, 2007)
The paper deals with combined finite/discrete element method to study structures under severe dynamic loading, like impact. The discrete element method take naturally into account the non linear phenomena, it is used in the vicinity of the impacted zone. The finite element method is used to reduce the time of computation in order to carry out large structure analyses. The aim of the paper is to discuss the way to reduce non physical wave reflections; it presents an application on a rock impact on a concrete slab.